Solusi Mengatasi Krisis Tanah Dan Pentingnya Pendaftaran Tanah Di Indonesia Dalam Mewujudkan Kepastian Hukum - Nathania, Nanda Riesta; Ismail, Zakiya Az Zikra; Ulum, M. Rivatul (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The land crisis in Indonesia has emerged as a critical issue, affecting socio-economic progress, environmental sustainability, and legal certainty. Factors such as rapid urbanization, population growth, and unregulated land use have intensified conflicts over land ownership and usage, underscoring the need for immediate and effective solutions. This paper explores the main causes of the land crisis, including the absence of formal land registration systems, insufficient regulatory frameworks, and weak enforcement mechanisms.The paper highlights the significance of land registration as a vital measure in establishing legal certainty and ensuring property rights for both individuals and communities.Through an analysis of various case studies and current policies, this paper proposes a comprehensive approach to tackling the land crisis. The approach includes strengthening land governance, streamlining registration processes, and encouraging community participation in land management.By implementing these solutions, the paper seeks to establish a comprehensive framework that addresses land-related conflicts while promoting sustainable development and equitable access to land. In conclusion, the paper emphasizes that efficient land registration and management are crucial for ensuring legal certainty and safeguarding landowners' rights in Indonesia, ultimately contributing to a more just and sustainable future.